Comparative Safety and Efficacy of Eight Antithrombotic Regimens for Patients With Atrial Fibrillation Undergoing Percutaneous Coronary Intervention - Liang, Bo; Zhu, Yong-Chun; Gu, Ning (Frontiers in Cardiovascular Medicine, 2022)
Background: Antithrombotic therapy for patients with atrial fibrillation (AF) undergoing percutaneous coronary intervention (PCI) is facing major treatment problems in clinical practice. Methods: To study the safety and efficacy of different antithrombotic regimens using a Bayesian network meta-analysis of randomized controlled trials. PubMed, Web of Science, Cochrane Central Register of Controlled Trials, Embase, and China National Knowledge Infrastructure were searched to identify randomized controlled trials comparing different antithrombotic regimens. Bayesian random-effects model was used in this study. The primary safety and efficacy outcomes were major bleeding according to the Thrombolysis In Myocardial Infarction (TIMI) criteria and trial-defined major adverse cardiovascular events (MACE), respectively. The secondary safety outcomes were combined TIMI major and minor bleeding, trial-defined primary bleeding events, and intracranial hemorrhage. The secondary efficacy outcomes were all-cause or cardiovascular mortality, myocardial infarction (MI), stroke, stent thrombosis, and hospitalization. Results: Five randomized studies were included. Total 11532 patients from the five trials were analyzed, of whom 8426 were male. Compared with the ORs for vitamin K antagonist (VKA) plus P2Y12 inhibitor, those for all safety outcomes were lower for apixaban plus P2Y12 inhibitor with no significances. No differences were found among the antithrombotic regimens in terms of the efficacy outcomes. Apixaban plus P2Y12 inhibitor was the highest ranking of safety outcomes. Conclusions: Apixaban plus P2Y12 inhibitor appears to be associated with fewer bleeding complications while preserving antithrombotic efficacy. Moreover, for most efficacy indicators, VKA plus P2Y12 inhibitor ranking is still very high.